2017
DOI: 10.17844/jphpi.v20i2.17907
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Melanin from Cuttlefish and Squid Ink

Abstract: AbstrakKelas Cephalopoda (seperti cumi-cumi dan sotong) memiliki tinta sebagai pertahanan dirinya. Penelitian ini bertujuan untuk membandingkan aktivitas antibakteri melanin dari tinta sotong (Sepia sp.) dengan tinta cumi-cumi (Loligo sp.) terhadap Escherichia coli. Ekstraksi dan pemurnian terhadap tinta sotong dan cumi-cumi dilakukan untuk mendapatkan melanin dengan menggunakan HCl 0,5 M secara mekanik. Melanin yang diperoleh diuji aktivitasnya terhadap E. coli dengan metode kontak langsung antara melanin dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…This can lead to irregular whole formation in the outer membrane and alter membrane permeability due to the gradual release of LPS molecules and membrane proteins. The results of this study are supported by previous research, which shows an increase in the value of optical density (wavelengths of 260 nm and 280 nm), to the administration of melanin extract on the growth of E. coli (Fitrial & Khotimah, 2017). The increase in optical density is closely related to the presence of bacteria, presumably due to the effect of melanin which inhibits bacterial growth by damaging cell walls (Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…This can lead to irregular whole formation in the outer membrane and alter membrane permeability due to the gradual release of LPS molecules and membrane proteins. The results of this study are supported by previous research, which shows an increase in the value of optical density (wavelengths of 260 nm and 280 nm), to the administration of melanin extract on the growth of E. coli (Fitrial & Khotimah, 2017). The increase in optical density is closely related to the presence of bacteria, presumably due to the effect of melanin which inhibits bacterial growth by damaging cell walls (Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…In 2017, a study conducted by Fitrial and Khotimah (2017) from Indonesia demonstrated that melanin from this cuttlefish ink has the potential to suppress 99.99% of E. coli bacteria at a concentration of 10 mg/mL. The antibacterial activity of Sepia sp.…”
Section: Sepia Spmentioning
confidence: 99%
“…A study states that cuttlefish ink has antibacterial activity (Nair et al, 2011). Several other researchers have also tested antibacterial activity on extracts from cuttlefish ink, the results of which say that the extract has inhibitory activity against several bacteria such as Pseudomonas aeruginosa, Staphylococcus epidermidis, Klebsiella pneumoniae and E. coli (Yuvaraj et al, 2015;Fitrial and Khotimah, 2017). It is presumably because cuttlefish ink has melanin content where melanin itself has antibacterial activity, although it has not been widely revealed.…”
Section: Antibacterial Testmentioning
confidence: 99%
“…It is presumably because cuttlefish ink has melanin content where melanin itself has antibacterial activity, although it has not been widely revealed. However, the melanin concentration of cuttlefish ink extract (0.010 g / mL) was able to kill bacteria so that after 24-hour incubation, there was only one living cell (inhibition reached 99.99%) (Fitrial and Khotimah, 2017). Besides, Vasantharaja et al (2014) reported that methanol extracts of Sepia sp.…”
Section: Antibacterial Testmentioning
confidence: 99%